Sacred consumption the religions of Christianity and consumerism in America - Mundey, Peter (Lanham Lexington Books, 2023)
"This book explores the quasi-religious nature of consumerism and how American Christianity interacts with consumerism. The author uses mixed methods to unpack the nexus between the Christian faith and consumption and how habitual discretionary consumption functions as a pseudo-faith in America"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Consumption (Economics) -- Religious aspects -- Christianity; Consumption (Economics) -- Religious aspects -- Christianity; Consumer behavior -- United States; Christianity and culture -- United States